Functions of Number Theory - 27.4 Euler Products and Dirichlet Series

From testwiki
Revision as of 12:06, 28 June 2021 by Admin (talk | contribs) (Admin moved page Main Page to Verifying DLMF with Maple and Mathematica)
(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)
Jump to navigation Jump to search


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
27.4.E3 ζ ( s ) = n = 1 n - s Riemann-zeta 𝑠 superscript subscript 𝑛 1 superscript 𝑛 𝑠 {\displaystyle{\displaystyle\zeta\left(s\right)=\sum_{n=1}^{\infty}n^{-s}}}
\Riemannzeta@{s} = \sum_{n=1}^{\infty}n^{-s}
s > 1 𝑠 1 {\displaystyle{\displaystyle\Re s>1}}
Zeta(s) = sum((n)^(- s), n = 1..infinity)
Zeta[s] == Sum[(n)^(- s), {n, 1, Infinity}, GenerateConditions->None]
Successful Successful Skip - symbolical successful subtest Successful [Tested: 2]
27.4.E3 n = 1 n - s = p ( 1 - p - s ) - 1 superscript subscript 𝑛 1 superscript 𝑛 𝑠 subscript product 𝑝 superscript 1 superscript 𝑝 𝑠 1 {\displaystyle{\displaystyle\sum_{n=1}^{\infty}n^{-s}=\prod_{p}(1-p^{-s})^{-1}}}
\sum_{n=1}^{\infty}n^{-s} = \prod_{p}(1-p^{-s})^{-1}
s > 1 𝑠 1 {\displaystyle{\displaystyle\Re s>1}}
sum((n)^(- s), n = 1..infinity) = product((1 - (p)^(- s))^(- 1), p = - infinity..infinity)
Sum[(n)^(- s), {n, 1, Infinity}, GenerateConditions->None] == Product[(1 - (p)^(- s))^(- 1), {p, - Infinity, Infinity}, GenerateConditions->None]
Failure Failure Error
Failed [2 / 2]
Result: Plus[2.612375348685488, Times[-1.0, NProduct[Power[Plus[1, Times[-1, Power[p, -1.5]]], -1]
Test Values: {p, DirectedInfinity[-1], DirectedInfinity[1]}, Rule[GenerateConditions, None]]]], {Rule[s, 1.5]}

Result: Plus[1.6449340668482262, Times[-1.0, NProduct[Power[Plus[1, Times[-1, Power[p, -2]]], -1]
Test Values: {p, DirectedInfinity[-1], DirectedInfinity[1]}, Rule[GenerateConditions, None]]]], {Rule[s, 2]}

27.4.E6 n = 1 ϕ ( n ) n - s = ζ ( s - 1 ) ζ ( s ) superscript subscript 𝑛 1 Euler-totient-phi 𝑛 superscript 𝑛 𝑠 Riemann-zeta 𝑠 1 Riemann-zeta 𝑠 {\displaystyle{\displaystyle\sum_{n=1}^{\infty}\phi\left(n\right)n^{-s}=\frac{% \zeta\left(s-1\right)}{\zeta\left(s\right)}}}
\sum_{n=1}^{\infty}\Eulertotientphi[]@{n}n^{-s} = \frac{\Riemannzeta@{s-1}}{\Riemannzeta@{s}}
s > 2 𝑠 2 {\displaystyle{\displaystyle\Re s>2}}
sum(phi(n)*(n)^(- s), n = 1..infinity) = (Zeta(s - 1))/(Zeta(s))
Sum[EulerPhi[n]*(n)^(- s), {n, 1, Infinity}, GenerateConditions->None] == Divide[Zeta[s - 1],Zeta[s]]
Failure Successful Error Successful [Tested: 0]
27.4.E9 n = 1 2 ν ( n ) n - s = ( ζ ( s ) ) 2 ζ ( 2 s ) superscript subscript 𝑛 1 superscript 2 number-of-primes-dividing-nu 𝑛 superscript 𝑛 𝑠 superscript Riemann-zeta 𝑠 2 Riemann-zeta 2 𝑠 {\displaystyle{\displaystyle\sum_{n=1}^{\infty}2^{\nu\left(n\right)}n^{-s}=% \frac{(\zeta\left(s\right))^{2}}{\zeta\left(2s\right)}}}
\sum_{n=1}^{\infty}2^{\nprimesdiv@{n}}n^{-s} = \frac{(\Riemannzeta@{s})^{2}}{\Riemannzeta@{2s}}
s > 1 𝑠 1 {\displaystyle{\displaystyle\Re s>1}}
sum((2)^(ifactor(n))* (n)^(- s), n = 1..infinity) = ((Zeta(s))^(2))/(Zeta(2*s))
Error
Error Missing Macro Error - -
27.4.E11 n = 1 σ α ( n ) n - s = ζ ( s ) ζ ( s - α ) superscript subscript 𝑛 1 divisor-sigma 𝛼 𝑛 superscript 𝑛 𝑠 Riemann-zeta 𝑠 Riemann-zeta 𝑠 𝛼 {\displaystyle{\displaystyle\sum_{n=1}^{\infty}\sigma_{\alpha}\left(n\right)n^% {-s}=\zeta\left(s\right)\zeta\left(s-\alpha\right)}}
\sum_{n=1}^{\infty}\sumdivisors{\alpha}@{n}n^{-s} = \Riemannzeta@{s}\Riemannzeta@{s-\alpha}
s > max ( 1 fragments 𝑠 fragments ( 1 {\displaystyle{\displaystyle\Re s>\max(1}}
sum(add(divisors(alpha))*(n)^(- s), n = 1..infinity) = Zeta(s)*Zeta(s - alpha)
Error
Failure Missing Macro Error
Failed [18 / 18]
Result: Float(infinity)
Test Values: {alpha = 3/2, s = -3/2}

Result: 5.224750698
Test Values: {alpha = 3/2, s = 3/2}

... skip entries to safe data
-
27.4.E13 n = 2 ( ln n ) n - s = - ζ ( s ) superscript subscript 𝑛 2 𝑛 superscript 𝑛 𝑠 diffop Riemann-zeta 1 𝑠 {\displaystyle{\displaystyle\sum_{n=2}^{\infty}(\ln n)n^{-s}=-\zeta'\left(s% \right)}}
\sum_{n=2}^{\infty}(\ln@@{n})n^{-s} = -\Riemannzeta'@{s}
s > 1 𝑠 1 {\displaystyle{\displaystyle\Re s>1}}
sum((ln(n))*(n)^(- s), n = 2..infinity) = - diff( Zeta(s), s$(1) )
Sum[(Log[n])*(n)^(- s), {n, 2, Infinity}, GenerateConditions->None] == - D[Zeta[s], {s, 1}]
Successful Successful - Successful [Tested: 2]